Consumer evaluation of public charging infrastructure for electric vehicles - Joachim Globisch; Patrick Plötz; Elisabeth Dütschke; Martin Wietschel (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2018)
The lack of public charging infrastructure is often referred to as an important barrier to the diffusion of electric vehicles. As the construction of charging stations is a costly endeavour, the question arises as to how maximum benefit for potential users can be achieved with limited resources. Therefore, our analysis deals with the factors that influence the attractiveness of public charging infrastructure from the perspective of potential users. Our analysis is based on the assessments of 1003 German car drivers on possible future charging infrastructure systems with different configurations regarding spatial coverage, charging duration and usage costs. We examined the preferences with regard to these features using a rating-based conjoint analysis. We also looked into the question of whether groups of car drivers can be identified that are characterised by specific preference constellations with regard to these features. Our key finding is that the majority of car drivers are unwilling to pay a basic fee for the possibility of using public charging infrastructure. Nevertheless, there are subgroups that value the public charging infra-structure more than other car drivers. In addition to implications for possible business models, this result indicates that public charging infrastructure could be important for attracting other target groups to electromobility besides classic early adopters of electric vehicles. Furthermore, our analysis shows that the charging duration at charging stations in cities and along the high-way has a strong influence on the evaluation of the public charging infrastructure. The spatial coverage with charging stations in cities and along the highway, on the other hand, has a weaker influence. A central conclusion from this is that the existence of fast-charging stations should be prioritized over a close-meshed coverage with charging points when the charging infrastructure is expanded than.
urn:nbn:de:0011-n-497713-14
Keywords: 330; public charging infrastructure; EVSE; user perspective; electric vehicle; willingness to pay; target groups